Intifada hits the headlines : how the Israeli press misreported the outbreak of the second Palestinian uprising - Dor, Danny, 1951- (Bloomington : Indiana University Press, 2004)
In this nuanced and detailed study of newspaper reporting during the escalation of the second Intifada in the fall of 2000, Daniel Dor shows how real events are subject to distortion and manipulation by the media. In an analysis of the heart of Israel's media establishment, he finds a wide gap between the reality reported by field reporters and the eventual newspaper accounts framed by editors. Dor argues it is the influence of fear, anger, ignorance, and a desire to please and to sell newspapers that threatens the freedom of the press in a liberal democracy.
Under Arafat's baton -- Make no mistake, Yasser -- The limits of restraint -- A fifth column -- In all their murderous ugliness -- We have turned every stone.
Includes bibliographical references (pages 175-177) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Mass media -- Political aspects -- Israel; Arab-Israeli conflict -- 1993- -- Mass media and the conflict; Arab-Israeli conflict -- 1993- -- Press coverage -- Israel; Press and politics -- Israel; Jews -- Israel -- Attitudes; Mass media; Conflit israélo-arabe -- 1993- -- Couverture de presse -- Israël.; Juifs -- Israël -- Attitudes; Médias.; mass media; SOCIAL SCIENCE -- Media Studies; Arab-Israeli conflict -- Mass media and the conflict; Arab-Israeli conflict -- Press coverage; Jews -- Attitudes; Mass media -- Political aspects; Press and politics; Israel; Palestijnse kwestie; Perswezen; Intifadah; Publieke opinie; Berichtgeving; Since 1993; Electronic book